Tuesdays with Morrie : an old man, a young man, and life's greatest lesson - Albom, Mitch, 1958- (New York : Doubleday, 1997)
Mitch Albom chronicles several months he spent regularly visiting a former college professor, Morrie Schwartz, during the elder man's final year of life. .
830
830
Accelerated Reader AR
Keywords: Schwartz, Morris S; Brandeis University -- Faculty -- Biography; Amyotrophic lateral sclerosis -- Patients -- United States -- Biography; Teacher-student relationships -- United States -- Case studies; Death -- Psychological aspects -- Case studies; Myotrophic Lateral Sclerosis; Death -- Psychological aspects; Myotrophic Lateral Sclerosis; Attitude to Death; Amyotrophic Lateral Sclerosis -- Patients -- United States -- Biography; Teacher-student relationships -- United States -- Case Reports; Death -- Psychological aspects -- Case Reports